Taking climate action: Measuring carbon emissions in the garment sector in Asia - Samantha Sharpe; Elsa Dominish; M. Cristina Martinez-Fernandez (International Labour Organization (ILO), 2022)
This paper examines carbon emissions across the garment sector as counted using the two prominent methodologies for calculating emissions - the life cycle assessment (LCA) and carbon accounting in line with the Greenhouse Gas Protocol. The purpose of this paper is to provide insight into where and why the carbon intensity of textiles and garments varies across the supply chain and where activities to decarbonize the sector should be prioritized.
Keywords: 330; green jobs; sustainable development; clothing and textile industries; partnerships